2014
DOI: 10.1016/j.heares.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations of brain grey and white matter in early deaf adults

Abstract: Functional and structural brain alterations in the absence of the auditory input have been described, but the observed structural brain changes in the deaf are not uniform. Some of the previous researchers focused only on the auditory areas, while others investigated the whole brain or other selected regions of interest. Majority of studies revealed decreased white matter (WM) volume or altered WM microstructure and preserved grey matter (GM) structure of the auditory areas in the deaf. However, preserved WM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 80 publications
9
68
1
Order By: Relevance
“…The present outcomes are in line with human literature demonstrating reduced white matter volume (Hribar, Suput, Carvalho, Battelino, & Vovk, 2014), correspondingly reduced myelination in the auditory cortex of congenitally deaf humans (Emmorey, Allen, Bruss, Schenker, & Damasio, 2003), and reduced cortical thickness in different regions of the brain of congenitally deaf humans (Li et al, 2012).…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…The present outcomes are in line with human literature demonstrating reduced white matter volume (Hribar, Suput, Carvalho, Battelino, & Vovk, 2014), correspondingly reduced myelination in the auditory cortex of congenitally deaf humans (Emmorey, Allen, Bruss, Schenker, & Damasio, 2003), and reduced cortical thickness in different regions of the brain of congenitally deaf humans (Li et al, 2012).…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…1). Similarly, prior brain morphology studies in adult SNHL patients (Shibata, 2007;Hribar et al, 2014) and SNHL children (Li et al, 2012) reported intact GM volumes of the auditory area in agreement with our study. Prior studies have demonstrated that non-auditory sensory information such as visual and tactile inputs activate the auditory cortex in SNHL (Lomber et al, 2010;Sadato et al, 2005), suggesting substantial plasticity of the auditory cortex during brain development.…”
Section: Audio-visual Interactionsupporting
confidence: 93%
“…In contrast, morphologic characteristics of gray matter (GM) in SNHL are controversial. Region‐based analyses showed no statistically significant changes in global and regional GM surface areas and volumes (Shibata, 2007; Hribar et al, 2014; Li et al, 2012), while a surface‐based study in children with SNHL reported decreased cortical thickness in the left precentral gyrus, right postcentral gyrus, left superior occipital gyrus, and the left fusiform gyrus (Li et al, 2012). Additionally, decreased GM volume in the cerebellum was reported in a voxel‐based analysis (Hribar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] A case of stroke with hearing loss that developed after bilateral ischemic lesions has been reported. 20) In that study, fiber tracking analysis revealed more severe fiber damage in the anterior part of the right hemisphere than in the left.…”
Section: Discussionmentioning
confidence: 99%